Nurse's leadership in the XXI century: some considerations - Galvão, Cristina Maria; Trevizan, Maria Auxiliadora; Sawada, Namie Okino (Revista da Escola de Enfermagem da USP, 1998)
The present article approaches the theme of leadership in it essential aspects and considers the transformations contemporary organizations are experiencing. Based on the literature authors found the role of the nurse-leader of the future and the importance of the auxiliary personnel-led to the efficacy of the leading process and the need of learning on leadership.